Tree cricket baffles are manufactured tools. (1st July 2018) - Mhatre, Natasha
Abstract: Tree crickets use sound to attract mates and make acoustic baffles to increase their sound production efficiency. It has been recently discovered that these insects use a flexible yet inherited behavioural programme to make acoustically optimal baffles. Whether these baffles qualify as tools, however, remains controversial. Here, baffle‐using and baffle‐making behaviours are analysed using the most current and authoritative definition of tool use. The current definition of tool use does not require the tool to be detached from the substrate and includes attached but manipulable external objects. Given this schema, tree cricket baffles, which are attached but manipulated prior to use, must be considered tools. The mode of manufacture for a baffle is "Subtract, " and the mode of use is "Drape".